The Influence of Transformational Leadership and School Environment on Academic Achievement of PAUD Teachers at West Pontianak District - Nazayanti Nazayanti; Wahyudi Wahyudi; M. Chiar (STKIP Singkawang, 2019)
.In general, this research departs from the researchers' thinking that with the better and higher Transformational leadership and school environment, the better and higher the Motivation for Achievement of teachers, especially in PAUD District of West Pontianak. The method used in this study is a type of causal study with a quantitative approach. The instrument used in this study is a questionnaire. The population in this study were Paud educators in West Pontianak Subdistrict with a total of 72 teachers from 26 Paud institutions in West Pontianak Subdistrict. The instrumentis divided into three variables: Transformational Leadership (X1), School Environment (X2), and Teacher Achievement Motivation (Y). Based on the analysis, the following results were obtained: first; the significance value of the Transformational Leadership variable (X1) is 0,000 or less than 0.05 so Ha is accepted and Ho Denied. It means that there is a significant influence of Transformational leadership on the achievement motivation of PAUD teachers in West Pontianak Subdistrict, with r X1y 0.66 and r table 0.229 Second; the significance value on the School Environment variable (X2) is 0.00 or less than 0.05 so that Ha is Accepted and Hois denied. It means that there is a significant influence on the School Environment on the achievement motivation of PAUD teachers in West Pontianak Subdistrict, with rX2y 0.685 with r table 0.229. And third; the value of the significance of Transformational leadership and school environment together is 0.00 or less than 0.05. Thus Ha is accepted,andHois rejected. It means that there is a significant influence of Transformational leadership and school environment together on teacher achievement motivation in the West Pontianak sub-district, with an r count of 47.868 and Ftable 3.13, at a significance level of 0.05. On the basis of the results of the study, it is expected that PAUD leaders or managers in West Pontianak Subdistrict should apply Transformational leadership well, it is hoped that the motivation of teachers to develop their existing potential will increase teachers should always spur themselves and continue to improve, develop potential and his achievements to improve the quality of education.